Ceramic composite based on zirconia reinforced by single-walled carbon nanotubes; Nanotechnologies in Russia; Vol. 14, iss. 3-4 - Leonov A. A. Andrey Andreevich; Dvilis E. S. Edgar Sergeevich; Khasanov O. L. Oleg Leonidovich; Paygin V. D. Vladimir Denisovich; Kalashnikov M. P. Mark Petrovich; Petyukevich M. S. Mariya Stanislavovna; Panina A. A. Aleksandra Anatolievna (2019, 2019)
Title screen